2014
DOI: 10.1037/ort0000010
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences between internationally adopted and nonadopted children in their toddler years: Outcomes from a longitudinal study.

Abstract: In this study, we compare internationally adopted children's communication, gross motor development, temperament, and challenging behavior with the same characteristics in nonadopted children at age 24 and 36 months. At 24 months, adopted children lag behind in communication and in gross motor development. The adopted children are less active and show less physically challenging behavior. At age 36 months, most of these differences have diminished, but the adopted children still lag behind in communication. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…Many adoptive families experience challenges that biological families may never face. Adopted children, whether domestic or international, face an increased likelihood of behavioral, emotional, developmental (Dalen & Theie, 2014; Jacobs, Miller, & Tirella, 2010), and attachment issues (Barcons et al, 2014) due to their unique pre-adoptive conditions (Weir et al, 2013). These conditions may include insufficient health-care and medical services; inadequate prenatal, perinatal, and postnatal care; psychological deprivation; abuse or neglect; early separation from the child’s birth mother; and malnutrition.…”
mentioning
confidence: 99%
“…Many adoptive families experience challenges that biological families may never face. Adopted children, whether domestic or international, face an increased likelihood of behavioral, emotional, developmental (Dalen & Theie, 2014; Jacobs, Miller, & Tirella, 2010), and attachment issues (Barcons et al, 2014) due to their unique pre-adoptive conditions (Weir et al, 2013). These conditions may include insufficient health-care and medical services; inadequate prenatal, perinatal, and postnatal care; psychological deprivation; abuse or neglect; early separation from the child’s birth mother; and malnutrition.…”
mentioning
confidence: 99%
“…Many IAY come from countries in which the native language that the children are exposed to early in life differs from the languages used in their post-adoption homes. Dalen and Theie (2014) compared IAY to non-adopted youth (NAY) during childhood. They found that IAY exhibited deficits in motor development and communication skills, lower activity levels, and greater reports of challenging behaviors at 24 months age; nevertheless, the only difference that remained at 36 months was a continuing deficit in communication skills.…”
Section: Country Of Originmentioning
confidence: 99%
“…This is expected because prior to achieving a complete catch-up, IA children tend to be more susceptible than their nonadopted age peers to difficulties with emotional regulation, social interactions, and problem solving (Jacobs, Miller & Tirella, 2010). Existing studies conducted in Europe and North America have concluded that IA children’s delays around the time of adoption increased their risk for poorer outcomes across multiple domains in early and middle childhood, including poorer parent–child relationship quality (Croft, O’Connor, Keaveney, Groothues, & Rutter, 2001; Dalen & Theie, 2014; Judge, 2003b, 2004; Niemann & Weiss, 2011; van Londen et al, 2007), poorer academic performance (Harwood, Feng, & Yu, 2013; Tan, 2009), and behavioral maladjustment (Cohen et al, 2008; Dalen & Theie, 2014; Palacios et al, 2011; Rutter & the ERA Study Team, 1998; Tan & Camras, 2011; Tan, Marfo, & Dedrick, 2007, 2010).…”
Section: Delays At Arrival and Later Outcomesmentioning
confidence: 99%